Pressure injury: development risks (Research, Society and Development, 2021)
The objective was to understand the risks of developing pressure injuries in the elderly. This is an integrative review, carried out from April to July 2021. The following descriptors were used: health professionals, pressure injuries and elderly health, in the bases: LILACS, MEDLINE and VHL. Twelve articles were found, of which the importance of understanding and qualifying the health team to act more effectively in the intervention of the topic addressed was highlighted, in order to improve care, preventing the development of these injuries. Through the findings discussed, it is clear that care practices tend to reduce the number of pressure injuries, in order to be treated mainly through prevention and curative treatment.